Influence Using the Project-Based Learning Model in History Learning on Learning Outcomes Student Class XI IPS MAN Temanggung - Ramadhany, Ardhian; Purnomo, Arif; Suryadi, Andy (Universitas Negeri Semarang, 2019)
This research discusses the influence of using a learning model learning project based on the teaching history of the study graders' results in Xi IPS Man Temanggung. The approach that was undertaken in the research is the quantitative approach, a quasi-experimental design. The population in the study was a student xi ips man Temanggung academic year 2015/2016; the sample in the research was a class XI social 1; this procedure used the sample collection using a random sample technique. The variable in this research is a project-based learning model and study results. Data collection method in a test, survey, and documentation. Search shows that study results showed students who use the project-based learning model have an average point pretest of 61.86 and a posttest increase of 82.94. Is the use of a learning model project-based learning of the results of the studied history. The size of the influence of the use of the learning model project-based learning is 23.8, showing that the use of the learning model project-based learning is the dominant factor in determining whether there is an increase or a failure in the study results.